2021
DOI: 10.1080/24721735.2021.1880204
|View full text |Cite
|
Sign up to set email alerts
|

Life in a pandemic: intersectional approach exploring experiences of LGBTQ during COVID-19

Abstract: The study explored the experiences of Indian working-class gays during the time of COVID-19 pandemic. The intersectionality framework facilitated the understanding of how the Indian working-class gays' experiences differ from the general population. The study is qualitative and applies transcendental phenomenology as a mode of enquiry. The participants of the study were identified through purposive snowball sampling. The data analysis methods included horizontalisation, thematic analysis, textual and structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 36 publications
0
12
0
1
Order By: Relevance
“…However, there may be protective factors such as resilience [15], which researchers should consider in future studies. Nevertheless, the COVID-19 pandemic seems to have emphasized the inequalities and disparities already existent in society [67,[71][72][73], leading to vulnerability situations that are particularly difficult for bisexual people [72]. Therefore, we can conclude that there are differences in the perception of WRQoL between sexual orientations, with a marked disadvantage for bisexuals, perhaps because the lack of visibility of bisexuality in society is associated with greater vulnerability and susceptibility to the influence of social stigma, particularly biphobia [74].…”
Section: Discussionmentioning
confidence: 92%
“…However, there may be protective factors such as resilience [15], which researchers should consider in future studies. Nevertheless, the COVID-19 pandemic seems to have emphasized the inequalities and disparities already existent in society [67,[71][72][73], leading to vulnerability situations that are particularly difficult for bisexual people [72]. Therefore, we can conclude that there are differences in the perception of WRQoL between sexual orientations, with a marked disadvantage for bisexuals, perhaps because the lack of visibility of bisexuality in society is associated with greater vulnerability and susceptibility to the influence of social stigma, particularly biphobia [74].…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, participants in this sample, who were mostly white and middle class and who had access to resources to assist them in managing COVID-19 regulations, discussed their relative privilege in comparison to other LGBTIQ people who may not have those same privileges, including those of lower socioeconomic status. Recent research has argued that COVID-19 has compounded and deepened social and health divides for people with multiple and layered vulnerabilities, such as those with minority sexual identities and low socioeconomic status (Bhalla & Agarwal, 2021; Chatterjee et al, 2020; Galea & Abdalla, 2020; Salerno et al, 2020). In such circumstances, not only might people need to consider their vulnerabilities as gay and bisexual men but they may also need to contend with pressures associated with low socioeconomic status, such as limited access to finances and ongoing housing.…”
Section: Discussionmentioning
confidence: 99%
“… 13 , 14 A rapidly growing literature has documented the impact of the pandemic on different aspects of LGBT people’s lives, including their mental health, 15–18 health behaviours 19–21 experiences of stigma and discrimination, 22 , 23 difficulties of accessing health services, 24–26 and economic hardship, 27 as well as their agency and resilience in dealing with the pandemic. 28–31 It has been found that, in general, LGBT people faced a disproportionate impact during the pandemic, compared with their heterosexual and cisgender counterparts. 18 , 32–35 Recent research has argued that the impact of different social positions, such as gender, race, ethnicity, socioeconomic status, and sexual and gender identity, on the experiences of the pandemic works intersectionally.…”
Section: Introductionmentioning
confidence: 99%
“… 31 , 36–39 Thus, an intersectionality framework is needed to understand the unique and disproportionate consequences of the pandemic on sexual and gender minority individuals, as well as the diverse experiences within the LGBT community. 28 , 31 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation